Territories : islands, camps and other states of Utopia - Biesenbach, Klaus; KW - Institute for Contemporary Art, Berlin (Berlin Köln : KW - Institute for Contemporary Art Berlin Verlag der Buchhandlung Walther König Köln, 2003)
Balaban, Amir ; Balaban, Sharon ; Bartana, Yael ; Bauer, Daniel ; Boeri, Stefano ; Buckingham, Matthew ; Careri, Francesco ; Efrat, Zvi ; Koester, Joachim ; Linke, Armin ; Misselwitz, Philipp ; Rotbard, Sharon ; Segal, Rafi ; Schaerf, Eran ; Snyder, Sean ; Weizman, Eyal
Korte biog. 294-297
This publication is published to accompany the exhibition "Territories : islands, camps and other states of Utopia" at the KW - Institute for Contemporary Art in Berlin, 01.06.2003 - 25.08.2003
boek